Insights of Heteroatoms Doping‐Enhanced Bifunctionalities on Carbon Based Energy Storage and Conversion. (23rd December 2020) - Wang, Xiaowei; Yang, Chao; Li, Jun; Chen, Xi'an; Yang, Keqin; Yu, Xiaochun; Lin, Dajie; Zhang, Qingcheng; Wang, Shun; Wang, Jichang; Xia, Zhenhai; Jin, Huile
Abstract: Ever‐developing energy storage technologies demand the pursuit of advanced materials with multiple functionalities. Recent studies revealed that multiple heteroatom‐doped carbon has been wildly used for bi‐functional or even tri‐functional energy storage and conversion. However, few efforts have been made to uncover the origin of multi‐functionalities. Herein, a nitrogen, phosphorus, and sulfur tri‐doped carbon is designed in this work with large porosity, rich heteroatoms doping and high mass density, exhibiting excellent bifunctionalities on supercapacitors and oxygen reduction reaction. Importantly, the density functional theory calculations demonstrate the relevant co‐doping and tri‐doping generate more active sites on neighboring carbon atoms than single doping, and the same type of active sites may enhance bifunctionalities simultaneously. The present investigations provide a promising guidance on the design of multi‐functional materials for future energy storage and conversion applications. Abstract : This report provides new insights of heteroatoms doping‐enhanced bifunctionalities on carbon based supercapacitors and oxygen reduction reactions. The study indicates that co‐doping and tri‐doping generate more active sites on neighboring carbon atoms than single doping, and the same active sites may enhance bifunctionalities simultaneously.